(untitled) (Acta Polytechnica CTU Proceedings, 2023)
The aim of this paper is focused on benefits of stereolithography (SLA) technology for the fabrication of the lightweight lattice structures with potential for load-bearing function and high absorption of impact energy. SLA is an additive manufacturing technology employing the principle of liquid resins curing moderated by radiation of a wavelength from ultra-violet band where resulting material parameters are tunable by setting of the curing process. The batches of samples manufactured using three different resins were subjected to quasi-static uni-axial tensile and compression tests. Acquired data were processed to derive deformation behaviour expressed as stress-strain diagrams and fundamental material properties. Based on the knowledge obtained from the mechanical tests, the setup of the fabrication parameters, the most suitable resin for manufacturing of the lattice structures and the overall suitability of SLA technology for the fabrication of advanced porous materials, were determined.